The Prevalence of Medical Conditions Among U.S. Chinese Community-Dwelling Older Adults - Dong, XinQi (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND. The burden of medical conditions is increasing among U.S. older adults, yet we have very limited knowledge about medical conditions among Chinese older adults in the United States. This study aimed to examine the prevalence of medical conditions and its sociodemographic and health-related correlates within the context of a population-based cohort study of U.S. Chinese older adults. METHOD. Using a community-based participatory research approach, community-dwelling Chinese older adults aged 60 years and older in the Greater Chicago area were interviewed between 2011 and 2013. RESULTS. Of the 3,159 participants interviewed, 58.9% were female and the mean age was 72.8 years. In total, 84.3% of older adults had one or more medical condition, 24.6% reported two conditions, 19.5% had three conditions, and 17.0% reported four or more conditions. A sizeable percentage of older adults had never been screened for dyslipidemia (24.4%) or had never been screened for diabetes mellitus (35.7%).For those who reported high cholesterol, 73.0% were taking medications when compared with 76.1% of those who reported having diabetes and 88.3% of those who reported having high blood pressure. Various sociodemographic and health-related characteristics were correlated with medical conditions. CONCLUSION. Medical conditions were common among U.S. Chinese older adults, yet screening and treatment rates were fairly low. Future longitudinal studies should be conducted to better understand the risk and protective factors associated with medical conditions.